Does fintech innovation promote enterprise transformation? Evidence from China. (February 2022) - Luo, Sumei; Sun, Yongkun; Yang, Fan; Zhou, Guangyou
Abstract: In the context of China's slowing economic growth and the rapid development of fintech, it is of practical significance to study the impact of fintech on the transformation of Chinese enterprises and economic sustainable development. We use the data of 2064 listed enterprises in China from 2012 to 2018 and based on the DEA Malmquist model to calculate the total factor productivity of the entities. The fintech development index was constructed by using text mining method and factor analysis to test the relationship between fintech innovation and enterprise transformation. The results show that fintech innovation effectively improves the total factor productivity of real enterprises, promotes the transformation, and upgrades the sustainable development of the real economy. The influence of fintech development on the transformation of entity enterprises is mainly through two mechanisms: information effect and resource allocation effect. Further research finds that the heterogeneity between the absorption capacity of large state-owned enterprises and small and medium-sized private enterprises to the promotion effect of fintech. In addition, small and medium-sized private enterprises are obviously stronger than large state-owned enterprises. Highlights: Explored the impact of fintech to the enterprise transformation. Total factor productivity of real enterprises calculated by DEA Malmquist model. Construct the Fintech development index by using text mining. The results show that fintech innovation promote enterprise transformation.